Non‐technical skills curriculum incorporating simulation‐based training improves performance in colonoscopy among novice endoscopists: Randomized controlled trial. Issue 6 (18th February 2020) - Walsh, Catharine M.; Scaffidi, Michael A.; Khan, Rishad; Arora, Anuj; Gimpaya, Nikko; Lin, Peter; Satchwell, Joshua; Al‐Mazroui, Ahmed; Zarghom, Omid; Sharma, Suraj; Kamani, Alya; Genis, Shai; et al.
Abstract : Background and Aims: Non‐technical skills (NTS), involving cognitive, social and interpersonal skills that complement technical skills, are important for the completion of safe and efficient procedures. We investigated the impact of a simulation‐based curriculum with dedicated NTS training on novice endoscopists' performance of clinical colonoscopies. Methods: A single‐blinded randomized controlled trial was conducted at a single center. Novice endoscopists were randomized to a control curriculum or a NTS curriculum. The control curriculum involved a didactic session, virtual reality (VR) simulator colonoscopy training, and integrated scenario practice using a VR simulator, a standardized patient, and endoscopy nurse. Feedback and training were provided by experienced endoscopists. The NTS curriculum group received similar training that included a small‐group session on NTS, feedback targeting NTS, and access to a self‐reflective NTS checklist. The primary outcome was performance during two clinical colonoscopies, assessed using the Joint Advisory Group Direct Observation of Procedural Skills (JAG DOPS) tool. Results: Thirty‐nine participants completed the study. The NTS group ( n  = 21) had superior clinical performance during their first ( P  < 0.001) and second clinical colonoscopies ( P  < .0.001), compared to the control group ( n  = 18). The NTS group performed significantly better on the VR simulator ( P  < 0.05) and in the integrated scenario ( P  < 0.05). Conclusion: Our findings demonstrate that dedicated NTS training led to improved performance of clinical colonoscopies among novices.